Resolution of Left Ventricular Thrombus Secondary to Tachycardia-Induced Heart Failure with Rivaroxaban - Kosuke Nakasuka; Shigenori Ito; Tsubasa Noda; Takahiro Hasuo; Satoru Sekimoto; Hiroyuki Ohmori; Masahiko Inomata; Takayuki Yoshida; Nozomu Tamai; Tomoaki Saeki; Shin Suzuki; Yoshimasa Murakami; et al. (Case Reports in Medicine)
A 42-year-old man was admitted to our hospital because of lumbago and tachycardia-induced heart failure. Transthoracic echocardiography revealed impaired left ventricular function and a ball mass of thrombus in the left ventricle (LV). He was found to have systemic embolism in the spleen, kidneys, brain, and limbs. The patient was treated with limb thrombectomy followed by anticoagulation. Seven days after the direct factor Xa inhibitor, rivaroxaban, was initiated, transthoracic echocardiography was repeated, revealing disappearance of the LV thrombus without any clinical signs of cardiogenic embolism. His heart failure responded well and the LV wall motion had improved. This case suggests rivaroxaban has fibrinolytic effects on thrombi even in the LV.